2023
DOI: 10.3390/ma16083220
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the SAG Grinding Process Using Statistical Analysis and Machine Learning: A Case Study of the Chilean Copper Mining Industry

Abstract: Considering the continuous increase in production costs and resource optimization, more than a strategic objective has become imperative in the copper mining industry. In the search to improve the efficiency in the use of resources, the present work develops models of a semi-autogenous grinding (SAG) mill using statistical analysis and machine learning (ML) techniques (regression, decision trees, and artificial neural networks). The hypotheses studied aim to improve the process’s productive indicators, such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 107 publications
0
7
0
Order By: Relevance
“…Figure 6 shows the scatter plot between the real values and the prediction of Wi (kWh/t), which shows a determination coefficient R2 of 98%. Saldaña, et al (2023), in their study, the adjustment through the application of artificial neural networks, for its part, turned out to be the model with the best adjustment indicators (MAE,RMSE and R2), where it obtained an R2 of 89%, whose architecture of the RNA corresponded to a multilayer perceptron. In this study, an R2 of 98% is a very strong indicator that the model is capable of making predictions very close to the real values of the variable Wi.…”
Section: Contrast Ann Results With Real Wi Datamentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 6 shows the scatter plot between the real values and the prediction of Wi (kWh/t), which shows a determination coefficient R2 of 98%. Saldaña, et al (2023), in their study, the adjustment through the application of artificial neural networks, for its part, turned out to be the model with the best adjustment indicators (MAE,RMSE and R2), where it obtained an R2 of 89%, whose architecture of the RNA corresponded to a multilayer perceptron. In this study, an R2 of 98% is a very strong indicator that the model is capable of making predictions very close to the real values of the variable Wi.…”
Section: Contrast Ann Results With Real Wi Datamentioning
confidence: 99%
“…Otsuki and Jang (2022), in their study collected a total of 56 data sets and randomly divided into training data sets (40 data sets: 70%), validation (8 data sets: 15%) and training (8 data sets: 15%), for their grinding study, 56 experimental data sets were considered more than enough. Saldaña, et al (2023), in their research divided the historical data into two groups, that is, the training set (70%) and the validation set (30%), while the fitted model was used to estimate the production after the application of the M2M strategy and simulate production, at different values of the mill rotation speed and lining age factors. Like Azizi, et al (2020), in their study to investigate the application of three powerful Kernel-based supervised learning algorithms to develop a global model of the wear rate of grinding media based on input factors such as pH, percentage of solids, the loading weight of the balls and the rotation speed of the mill and the grinding time, the models were trained using 40 randomly selected data (representing 80% of the total data) and the remaining 10 data (which represent 20%) were applied for testing purposes.…”
Section: Contrast Ann Results With Real Wi Datamentioning
confidence: 99%
See 1 more Smart Citation
“…[18] for intelligence-based hybrid approaches, and Ref. [19] where a compelling case study is provided that leverages machine learning techniques to enhance SAG mill productivity indicators such as production and energy consumption. A great review on this subject can be found in [20], where a rigorous discussion on the topic is provided.…”
Section: Introductionmentioning
confidence: 99%
“…Delaney et al [47] used various methods to implement predictive analytics techniques as a result the model estimates mass loss with particle evolution and included cumulative damage and destruction. Saldana et al [48] considered optimization of particle fracture processes using machine learning, which can significantly improve the quality of control.…”
mentioning
confidence: 99%